Behavioral resilience in the post-genomic era: emerging models linking genes with environment - Rende, Richard (Frontiers in Human Neuroscience, 2012)
One of the most important deliverables of the post-genomic era has been a new and nuanced appreciation of how the environment shapes – and holds potential to alter – the expression of susceptibility genes for behavioral dimensions and disorders. This paper will consider three themes that have emerged from cutting-edge research studies that utilize newer molecular genetic approaches as well as tried-and-true genetic epidemiological methodologies, with particular reference to evolving perspectives on resilience and plasticity. These themes are: 1) evidence for replicable and robust shared environmental effects on a number of clinically relevant behaviors in childhood and adolescence; 2) evolving research on gene-environment interaction; and 3) a newer focus on differential susceptibility and plasticity. The net sum of these themes is that consideration of genetic effects on behavioral dimensions and disorders needs to be connected to thinking about the role of environment as a potent source for promoting resilience and change.